Motor skills of girls and boys from various residential environments - Eider, J. (Education. Physical training. Sport, 2000)
The aim of this research has been to determine motor skills of girls and boys from various residential environments. The research has covered 278 children aged from 7 to 8 from Szczecin and the Province of Western Pomerania. That group includes girls and boys from cities (n=99), children from the country (n=91) and city children doing sport (n=88). The training period has been 8 months for 7-year-old girls and boys and 18 months for children aged 8. In order to determine motor skills of the tested children all tests included in the International Fitness Test have been carried out. Results (specified in seconds, centimeters, meters, kilograms or a number of tasks performed) have been converted into points according to the T scale, covering the range from 0 to 100. A score achieved informs of the position of a given motor test result in relation to the average result converted into points, i. e. 50 points. The obtained results have been processed by basic statistic methods. As it appears from the analysis of the research material children aged from 7 to 8 possess better motor skills than their contemporaries from cities or from the country who do not practice any sport. The latter have a little better speed skills than their country contemporaries. Children from the country are a little better at strength skills and their running stamina is a little better.